2017
DOI: 10.1289/ehp806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inorganic Arsenic, Methylated Arsenicals, and Arsenobetaine on Atherosclerosis in the apoE−/− Mouse Model and the Role of As3mt-Mediated Methylation

Abstract: Background:Arsenic is metabolized through a series of oxidative methylation reactions by arsenic (3) methyltransferase (As3MT) to yield methylated intermediates. Although arsenic exposure is known to increase the risk of atherosclerosis, the contribution of arsenic methylation and As3MT remains undefined.Objectives:Our objective was to define whether methylated arsenic intermediates were proatherogenic and whether arsenic biotransformation by As3MT was required for arsenic-enhanced atherosclerosis.Methods:We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…In addition, KO mice are at an increased risk for arsenic toxicities ( Douillet et al. 2017 ; Negro Silva et al. 2017 ; Yokohira et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KO mice are at an increased risk for arsenic toxicities ( Douillet et al. 2017 ; Negro Silva et al. 2017 ; Yokohira et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that As exposure could cause molecular and cellular events relevant to atherogenesis in cultured endothelial cells (Simeonova and Luster 2004) and also increase atherosclerotic plaque formation in ApoE/ mice (Negro Silva et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…All experiments related to animals were approved by the institutional animal care and use committee of Peking University and followed the guidelines for animal experiments of the university as well as for experimental animals in China. The biological effect size of the animal experiments was based on the previous paper (Negro Silva et al. 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Because the formation of atherosclerosis lesions required a long time, the exposure period used in the present study was based on previous studies in which the effects of chemicals on formation of atherosclerosis lesions were observed after an exposure period of 12–15 weeks (Li et al. 2009; Negro Silva et al. 2017; Shi et al.…”
Section: Methodsmentioning
confidence: 99%